Business Model Canvas Training in Business Development - I Gede Marendra; I Made Aryata; Irmawan Afagani; Gina Ramayanti (Jurnal Pengabdian Pancasila (JPP), 2024)
The current development of technology has made business competition even tighter where many new businesses have emerged to meet customer needs. Where based on the results of the Digital Creative Industry Society report, the number of technology startups in Indonesia is around 992 start-ups in Indonesia. One of the supports for the success of a startup is funding support, to get funding, startup owners must be able to convey their business ideas so that they are easy to understand and accept by investors. One of the tools used to visualize business ideas is the Business Model Canvas. Business Model Canvas training for UNSERA Industrial Engineering students is expected to be additional knowledge for students when developing business ideas through the Business Model Canvas approach.